Impact of the ongoing conflict on smallholder farmers in Sudan: Evidence from a nationwide survey - Kirui, Oliver K.; Siddig, Khalid; Ahmed, Mosab O. M.; Abushama, Hala; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2023)
This study addresses the impact of the ongoing conflict in Sudan on smallholder farmers' intentions and challenges during the 2023 summer agricultural season. A nationally representative survey of 3,284 smallholder farmers was conducted. Due to the security hazards and connectivity challenges, we used a combination of three interview types, Interactive Voice Recording (IVR), Computer-Assisted-Tele phone-Interviews (CATI) and face-to-face (in-person) interviews. Key findings are that close to a third of the farmers were displaced from their farms’ locations and 40 percent were unable to prepare for plant ing season because of the conflict. Most of the farmers who did not prepare for the summer season at the time of the interview were not intending to plant later in the season. The key challenges that pre vented them from planting were the lack of finance to buy agricultural inputs (such as seeds and fertiliz ers) and/or to hire farm labor. This is compounded by bad weather conditions, poor quality of the local seed varieties, higher cost of improved seeds, and delayed rains (climate challenges). In addition, the ongoing conflict has had direct and indirect impacts that prevented many farmers from planting this season. It disrupted market functionality and reduced the availability of and/or raised the cost of agricul tural inputs and farm labor. The lack of finances has also seen farmers reduce the size of the area they planted this season compared to last year’s season. The compounding challenges of these reduced production are expected to be felt as soon as the harvest season begins. The implications suggest the need for rapid intervention to support farmers during the harvest and winter seasons to mitigate the im pact of the conflict on agricultural activities.